Achieving the goal of the “4‰ initiative” and agricultural sustainability by co-incorporating rice straw and Chinese milk vetch for rice production in southern China - Yu Zhang; Wangwang Zhang; Fei Xu; Yuhang Qin; Hao Chen; Yuhong Wu; Shuo Li (Geoderma)
The co-incorporation of rice straw (RS) and Chinese milk vetch (CMV) has been suggested as an optimized agronomic management strategy to improve soil organic carbon (SOC) storage and agricultural sustainability. This study was designed to evaluate effects of co-incorporating RS and CMV (RS-CMV) on rice grain yields, sustainable yield index (SYI), economic benefit, the sequestration and stratification of SOC, carbon fractions, and the achievement of the 4 ‰ initiative, especially under lowering 30 % N rate in southern China. Four-year field experiments were designed and implemented with four treatments: no straw incorporation as the control (CK), RS incorporation (RSI), RS-CMV, and lowering 30 % N rate based on RS-CMV (RS-CMVL). Results showed that the RS-CMV exhibited the largest annual average rice grain yields, SYI, and economic profit, higher by 6.2 ∼ 9.4 %, 6.4 ∼ 9.2 %, and 6.4 ∼ 16.8 %, respectively, than those of CK and RSI, and had no obvious discrepancy with the RS-CMVL. Throughout the 0–40 cm soil profile, the RS-CMV and RS-CMVL significanly enhanced SOC storage by 12.5 % and 12.0 % relative to the CK, by9.1 % and 8.6 % relative to the RSI, and by 10.0 % and 9.6 % relative to the pre-experimental soil (2018), respectively. The C sequestered rate per 1000 reached 25.1 ‰ year−1 and 23.9 ‰ year−1 under RS-CMV and RS-CMVL, while no difference existed between RS-CMVL and RS-CMV. As well, the RS-CMV led to the highest storages of soil labile organic carbon fractions (LOCs), especially the highly labile organic carbon, while the RS-CMVL sequestered the largest recalcitrant organic carbon throughout the entire 0–40 cm soil layer. The RS-CMV increased the stratification ratio of LOCs, while no obvious discrepancy was observed when evaluating the SR of SOC. What’s more, the cumulative carbon and nitrogen inputs are highly correlated with the storages of SOC and its LOCs, and the SYI. The co-incorporation of RS and CMV, even under lowering 30 % N rate, was mainly responsible for the improvements of rice grain yields, sustainable yield index, economic profit, SOC and its fractions’ storage, and therefore could enhance SOC sequestration and agricultural sustainability, effectively achieving the goal of the “4‰ initiative”.